ADAT PERNIKAHAN DAYAK TOBAG TINJAUAN ANTROPOLINGUISTIK - NFN Martina (Balai Bahasa Kalimantan Barat, 2020)
This research was Indigenous Marriage Day of Tobag, Anthropolinguistic Review. The problem in this study is how anthropolinguistic studies are able to dissect on tradition and produce a neat analysis of the relationship between the two. In the discussion there are three main approaches in the study of anthropolinguistics, namely the performance (performance), indexicality (indexicalty), participation (participation), which proved effective in examining the relationship of text structure, context and context (culture, ideology, social, and situation) an oral tradition which is based on different cultural elements and aspects of human life. Anthropolinguistic studies, namely the emphasis of anthropolinguistics in exploring the meaning, function, values, norms, and local wisdom of an oral tradition, the concept of all three can be distinguished. More than that, the anthropolinguistic approach is able to formulate a model of revitalization and preservation of an oral tradition. In this case the distinguishing features of anthropolinguistic studies with other approaches are strong and prominent. The method used is descriptive analysis with a qualitative approach. This research is a literature or literature study which is supported by various research results. The results of the analysis show that local wisdom in the tradition terms sanggan bebayo ', tonya' menonya ', betunang, kebabar), (beloki bebini mbio lopas, beboki bebini bepipis becale'k abis man manu'k, beboki bebini ponoh, beloki bebini), and customary law are divided into four, namely customary social relations and issues (adat timpak kemata labat ka oti, nganggoh adat, betama'k kediri custom, nggagap custom), there are seven mas, adat sara'k or divorce (adat adat tabat kemabat labat oti, adat nganggoh, adat betama'k kediri, adat nggagap), there are seven mas, adat sara'k or divorce (adat adat). sara'k ingka ', sara'k siko'nngi like, sara'k timpak, sara'k creep, nula'k loki/chant and hand in hand), and adat amar (amar lawing agong adat, amar pesirah adat, amar jata crawl adat, amar temenggung adat, and amar pati adat).